2020
DOI: 10.1038/s41594-020-0383-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for RNA polymerase III transcription repression by Maf1

Abstract: Maf1 is a conserved inhibitor of RNA polymerase III (Pol III) that influences phenotypes from metabolic efficiency to lifespan. Here, we present a 3.3 Å cryo-EM structure of yeast Maf1 bound to Pol III, establishing that Maf1 sequesters Pol III elements involved in transcription initiation and binds the mobile C34 WH2 domain, sealing off the active site. The Maf1 binding site overlaps with that of TFIIIB in the pre-initiation complex.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Finally, functional studies of POLR3A mutations associated with POLR3-HLD have demonstrated transcriptional defects when introduced in both yeast and human cells (Choquet et al, 2019a ; Moir et al, 2020 ). Further research on molecular pathways and other POLR3 interactors will be valuable in determining whether suppression of upstream POLR3 inhibitors, such as MAF1 (Reina et al, 2006 ; Johnson et al, 2007 ; Bonhoure et al, 2020 ; Vorländer et al, 2020 ), are appropriate for future treatments. It is also possible that a small molecule screening approach could identify drugs for the treatment of specific molecular mechanisms, such as upregulation of complex assembly cofactors or signaling molecules for nuclear import of POLR3 (Cloutier and Coulombe, 2010 ; Lesniewska and Boguta, 2017 ; Willis and Moir, 2018 ).…”
Section: Polr3-related Leukodystrophy: Approaching Treatment Optionsmentioning
confidence: 99%
“…Finally, functional studies of POLR3A mutations associated with POLR3-HLD have demonstrated transcriptional defects when introduced in both yeast and human cells (Choquet et al, 2019a ; Moir et al, 2020 ). Further research on molecular pathways and other POLR3 interactors will be valuable in determining whether suppression of upstream POLR3 inhibitors, such as MAF1 (Reina et al, 2006 ; Johnson et al, 2007 ; Bonhoure et al, 2020 ; Vorländer et al, 2020 ), are appropriate for future treatments. It is also possible that a small molecule screening approach could identify drugs for the treatment of specific molecular mechanisms, such as upregulation of complex assembly cofactors or signaling molecules for nuclear import of POLR3 (Cloutier and Coulombe, 2010 ; Lesniewska and Boguta, 2017 ; Willis and Moir, 2018 ).…”
Section: Polr3-related Leukodystrophy: Approaching Treatment Optionsmentioning
confidence: 99%
“…Lipid accumulation of C. elegans in response to UV light exposure Although Maf1 function, and its role in the DNA damage response (DDR), has been widely researched in cultured yeast and mammalian cell models (Ghavidel and Schultz, 2001;Pluta et al, 2001;Upadhya et al, 2002;Reina et al, 2006;Johnson et al, 2007;Goodfellow et al, 2008;Vannini et al, 2010;Palian et al, 2014;Lee et al, 2015;Li et al, 2016;Shetty et al, 2020;Vorlander et al, 2020), fewer studies have been carried out in whole animals (Marshall et al, 2012;Khanna et al, 2014;Bonhoure et al, 2015;Pradhan et al, 2017). To test whether C. elegans mafr-1 mediates organismal responses to UV light exposure, we analyzed animals carrying the CRISPR/Cas9-mediated deletion of the entire mafr-1 locus, hereafter referred to as mafr-1 knockout (KO), as compared with wild-type (WT) control animals.…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of these functions is associated with the molecular under-pinnings of various disease states, which can lead to obesity, metabolic disease, or cancer (Willis and Moir, 2007;Khanna et al, 2015;Johnson and Stiles, 2016). Maf1 physically associates with TFIIIB and RNA pol III and prevents its transcription of rRNA, noncoding RNA (ncRNA), and (primarily) tRNA (Vannini et al, 2010;Vorlander et al, 2020). Study on glioblastoma cells reveals that Maf1 also regulates a subset of RNA pol I and pol II gene targets (Johnson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is negatively regulated via phosphorylation by the mTOR pathway and tailors 5S rRNA and tRNA production in response to various environmental cues [ 60 ]. Recent data have shown that the Maf1 binding site on Pol III overlaps with that of TFIIIB in the preinitiation complex [ 61 ]. Deletion of maf1 in the budding yeast Saccharomyces cerevisiae but not its homologue mafr-1 in C. elegans prevents dietary restriction or caloric restriction to extend lifespan.…”
Section: Lifespan Effects Of Mtor Through Regulation Of Gene Transmentioning
confidence: 99%